DNA Nanotechnology: A foundation for Programmable Nanoscale Materials. (8th December 2017) - Bathe, Mark; Rothemund, Paul W.K.
Abstract: Abstract : DNA nanotechnology is a materials design paradigm in which synthetic nucleic acids are used to program the structure and dynamics of nanometer-scale devices and materials. Driven by the convergence of decreasing DNA synthesis costs, advanced yet easy-to-use computational design and analysis tools, and, most importantly, a myriad of innovative studies demonstrating DNA's extraordinary power to organize functional materials, DNA nanotechnology is spreading into diverse areas of traditional materials science. To further promote the integration of DNA nanotechnology into materials science, this issue of MRS Bulletin provides an overview of the unique capabilities offered by DNA nanotechnology, a set of practical techniques that make it accessible to a broad audience, and a vision for its future applications, described by international leaders in the field.